Individual and interpersonal correlates of changes in college adaptation among Chinese freshmen: A longitudinal study - Li, Jian-Bin; Wang, Ying-Shuang; Sun, Yao; Liang, Yue; Dou, Kai (Current psychology (New Brunswick, N.J.), 2023)
Adaptation is an important issue in freshmen at the beginning of college life. Existing research on this topic has heavily relied on cross-sectional design and focused on the role of individual and family factors. Few studies have employed longitudinal design and focus on non-family contextual factors such as peers and teachers. This study aimed to explore the changes in academic, social, and personal-emotional adaptation throughout the first year of college and the associated individual (i.e., self-control, presence of life meaning, coping style, and allocentrism) and interpersonal (i.e., friendship quality and teacher-student relationship) correlates. Participants were Chinese freshmen recruited from two colleges in Southern China. They answered questionnaires on an online survey website at the second and eighth month after entering college (final N = 843). The results showed that academic adaptation did not change significantly over time, while social adaptation showed a significant decrease and personal-emotional adaptation showed a significant increase. Moreover, after controlling for respective baseline levels, each type of adaptation was predicted by a few factors. Noticeably, self-control positively predicted changes in all types of adaptation. In sum, the findings suggest that academic, social, and personal-emotional adaptation show different patterns of changes among Chinese college freshmen and that good self-control is a crucial factor that facilitates better college adaptation.